2009
DOI: 10.1177/1352458509103610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parenteral cladribine on relapse rates in patients with relapsing forms of multiple sclerosis: results of a 2-year, double-blind, placebo-controlled, crossover study

Abstract: Cladribine was well tolerated and associated with a favorable safety profile. Mean Expanded Disability Status Scale scores remained stable. In group A, mean relapse rates were 0.15 in year 1 (cladribine) and 0.42 in year 2. In group B, relapse rates were 0.61 in year 1 and 0.50 in year 2 (cladribine). PATIENTS required fewer steroid courses during cladribine periods. The therapeutic efficacy of cladribine was associated with a sustained reduction in lymphocyte count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…AEs reported more often with cladribine than placebo treatment were hypertonia; purpura, muscle weakness and upper respiratory tract infections. 29 No serious adverse events (SAEs) related to cardiotoxicity, nephrotoxicity or neurotoxicity were reported in the Scripps studies, consistent with the observation in oncology patients. As expected from its mechanism of action, cladribine treatment significantly reduced the number of leukocytes in these studies.…”
Section: Safety and Tolerabilitysupporting
confidence: 73%
See 1 more Smart Citation
“…AEs reported more often with cladribine than placebo treatment were hypertonia; purpura, muscle weakness and upper respiratory tract infections. 29 No serious adverse events (SAEs) related to cardiotoxicity, nephrotoxicity or neurotoxicity were reported in the Scripps studies, consistent with the observation in oncology patients. As expected from its mechanism of action, cladribine treatment significantly reduced the number of leukocytes in these studies.…”
Section: Safety and Tolerabilitysupporting
confidence: 73%
“…Cladribine was generally well-tolerated in the individual Scripps studies in MS. 29,30 In a pooled analysis of the data with cladribine vs placebo from the three Scripps studies and an additional supportive study in patients with MS, the most commonly reported treatment-emergent AEs were upper respiratory tract infections (32 vs 24%), headaches (28 vs 38%) and injection-site reactions (24 vs 25%). 27 There was a small dose-related increase in the frequency of upper respiratory tract and urinary tract infections (UTIs).…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Small placebo-controlled trials have demonstrated the efficacy of cladribine in delaying disease progression in patients with chronic progressive MS [67,68] or RRMS [69,70]. A 2-year double-blind, placebo-controlled crossover trial with 84 relapsing patients demonstrated that mean EDSS scores remained stable during the 2-year period, and cladribine reduced relapse rates [71]. Adverse events included lymphopenia, headache and naso pharyngitis [71].…”
Section: Cladribinementioning
confidence: 99%
“…A 2-year double-blind, placebo-controlled crossover trial with 84 relapsing patients demonstrated that mean EDSS scores remained stable during the 2-year period, and cladribine reduced relapse rates [71]. Adverse events included lymphopenia, headache and naso pharyngitis [71]. A Phase III clinical trial of oral cladribine monotherapy (CLARITY), which was a 2-year (96 weeks), randomized, double-blind, placebo-controlled international trial, enrolled 1326 patients with RRMS according to the revised McDonald criteria [72].…”
Section: Cladribinementioning
confidence: 99%
“…Over 18 months of follow-up, cladribine was associated with an improvement in relapse rate, relapse severity and MRI measures of disease activity 19. Another phase II randomised 84 people with relapsing MS to subcutaneous cladribine or placebo for 1 year, followed by a crossover in year 2 20. Cladribine was associated with a reduction in the annualised relapse rate (0.15 vs 0.42 in year 1) and some evidence of residual benefit persisting after treatment discontinuation; the relapse rate in the initial active-treatment arm was 0.42 in year 2 compared with 0.86 at baseline 20…”
Section: Introductionmentioning
confidence: 99%